Bentonite and Montmorillonite maturation with Águas de Lindóia, Peruíbe and Poços de Caldas waters (Brazilian Journal of Radiation Sciences (BJRS), 2019)
This study aims to characterize the artificial peloid obtained by maturing bentonite and montmorillonite with Águas de Lindóia, Poços de Caldas and Peruíbe water for three months. The pH, moisture, organic matter content, loss on ignition and swelling power of matured and non-matured samples were measured for physicochemical characterization. The elemental concentration was determined by instrumental neutron activation analysis. Results showed that pH, moisture (%) and LOI (%) at 1000 ºC did not changed after maturation for all samples and an increase in the organic matter (%) was noted for all samples, mainly in the peloids treated with Peruíbe sea water. The concentration of As, Ba, Br, Ca, Ce, Co, Cr, Cs, K, La, Na, Yb and Zn has changed after the maturation process in both clays and the Br and Na concentration has changed in both clays when matured with sea water from Peruíbe.